An Anodized Titanium/Sol-Gel Composite Coating with Self-Healable Superhydrophobic and Oleophobic Property - Li, Tinghua; Dong, Chongjian; Liu, Yupeng; Wu, Jun; Zhang, Xia; Gong, Xiaowei; Zhao, Wei; Wang, Daoai; Zhu, Donglai (Frontiers in Materials, 2021)
Superhydrophobic and oleophobic surfaces have attracted increasing attention because of their self-cleaning properties. A composite coating composed of anodized titanium and sol-gel (TiAO/SG) was developed and has good superhydrophobic and oleophobic property. The anodized titanium coating was prepared on the titanium substrate and then a sol-gel layer was coated on the surface of the anodized titanium layer to obtain a composite coating with superhydrophobic and oleophobic properties. The adhesion weight of glycerol on the surface of the superhydrophobic titanium wire decreased to 4.8% of that of untreated titanium wire, which showed that the material had good oleophobic property. This new composite coating could achieve self-healing superhydrophobicity by releasing loaded perfluorodenytriethoxysilane to the surface of the coating. Given its superhydrophobicity, self-healing and wear resistance, the TiAO/SG coating was expected to achieve healable self-cleaning protection in titanium devices.